Laurel British drama; the 20th century - Corrigan, Robert W. (Dell Publishing Company New York, 1965)
The twentieth Century is the first volume to appear in the Laurel British drama series, which will present the outstanding plays of that country from medieval times to the present.
Keywords: English drama -- History and criticism. -- 20th century